Remember the giver(s): the creation of the Querelle and notions of sender and recipient in University of California, Berkeley, MS 109 - Heather Bamford (Atalaya)
The Querelle, or the debate that ensued over interpretations of the Roman de la Rose between Christine de Pizan, Jean Gerson, Jean de Montreuil, and Gontier Col, marks an important event in the history of literary criticism. This paper is a reading and description of one of the most provocative, yet perhaps lesser known testimonies of Christine de Pizan’s version of the debate, Les epistres du debat sus le romant de la rose, as presented in University of California, Berkeley Bancroft Library MS 109 (UCB 109). The study of this manuscript and the texts contained therein discusses several of the many questions raised in the production and circulation of a book of carefully arranged letters: the creation of unique notions of author, scribe, and truth, as well as the complication of categories of sender and recipient.